UJI PEMADATAN STANDAR DAN UJI PEMADATAN MODIFIED TERHADAP TANAH YANG DICAMPUR KAPUR - Nurmaidah Nurmaidah; Suranto Suranto (Universitas Medan Area, 2022)
Compaction in the laboratory produces the maximum dry volume weight achieved at a certain water content. Compaction test is very dependent on the type of soil, water content and effort given during compaction. The effort given (compaction energy) is very dependent on the number of layer collisions, number of layers, pounder weight, pounder fall height and mold volume. The higher the effort given, the higher the volume of dry volume achieved. In laboratory mechanics soil compaction can be done by two methods, namely compaction with Standard Proctor and Modified Proctor. This study aims to obtain comparison results of the value of maximum dry density and optimum moisture content by using the Standard Proctor and Modified Proctor methods on land from Jalan Pertahanan - Patumbak mixed with Lime. The results of the analysis of the experiments obtained from the Road of Pertahanan - Patumbak soil by passing No. 200 loss 40.06%, Liquid Limit (LL) 31.60%, Plastic Limit (PL) 16.87%, Plastic Index (PI) 14, 73%. According to the Unified Soil Classification (USCS) this land is included in the CL-an organic symbol with low to moderate plasticity, while according to the Association of State Highway and Transportation Officials (AASHTO) this land is classified into group A-6 where this land is widely available and is often used as embankment material. Results of compaction experiments using the ASTM D-698 Standard Proctor AASHTO T-99 test obtained maximum dry density of 1.931 gr / cm3, optimum moisture content of 11.90%. whereas, with the testing of Modified Proctor ASTM D-1557 AASHTO T-180, the maximum dry density was 1.946 gr / cm3, the optimum moisture content was 12.1%. The values obtained show that the use of the ASTM D-1557 AASHTO T-180 Modified Proctor method is higher than the ASTM D-698 AASHTO T-99 Standard Proctor method